2012
DOI: 10.7166/19-1-113
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of a Locally Developed Cassava Chipping Machine

Abstract: A cassava chipping machine was designed and constructed, and its performance evaluated. The results showed that motor speed has significant effects on chipping capacity, chipping efficiency, and chips geometry. The higher the motor speed, the higher the chipping capacity and the lower the chipping efficiency of the machine. The machine has a maximum capacity of 245 kgh -1 at 500 rpm, and maximum chipping efficiency of 92.6% at a speed of 300 rpm. The overall best performance of the machine is obtained at a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
3
8
0
Order By: Relevance
“…The performance of a locally fabricated rice-milling machine was evaluated to determine the behavior of different paddy varieties at different conditions during milling. Performance test revealed that the milling efficiency, cleaning efficiency, input capacity, output capacity and average percentage of head rice yield obtained were 90.22%, 90.2%, 27.3kg/hr, 16.47kg/hr, and 44.2%, respectively (Dauda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The performance of a locally fabricated rice-milling machine was evaluated to determine the behavior of different paddy varieties at different conditions during milling. Performance test revealed that the milling efficiency, cleaning efficiency, input capacity, output capacity and average percentage of head rice yield obtained were 90.22%, 90.2%, 27.3kg/hr, 16.47kg/hr, and 44.2%, respectively (Dauda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cassava processing into chips aids in the rapid drying of the crops lowers its bulk density and eases its packaging, transportation and export. Some designs of cassava chippers have been presented in literature (Adejumo et al, 2001;Adewumi et al, 2005;Bolaji et al, 2008;Ndunguru et al, 2009;Ndukwu et al, 2019a); however, there is a scarcity of information on optimum operational parameters for the machine capacities and thickness of cassava chips produced under the operating conditions. The diminutive shelf-life and cumbersomeness of cassava roots pose a major challenge when it is transported from the field to the market or industrial locations due to its extremely perishable nature.…”
Section: Introductionmentioning
confidence: 99%
“…The second phase is the secondary or microbial deterioration which usually occurs 5 to 7 days after harvest. It involves wide spectrum of fungi and bacteria, which develop in the flesh, causing a variety of wet and dry rots [17,18]. This rapid post-harvest deterioration of cassava roots places serious constraints on their distribution and use, especially where there are delays in marketing, and on the holding of buffer stocks for large-scale processing.…”
Section: Introductionmentioning
confidence: 99%